Development and validation of high-performance liquid chromatography method for determination of some pesticide residues in table grape - Velkoska-Markovska, L.; Petanovska-Ilievska, B.; Jankulovska, M. S.; Ilievski, U. (Akademiai Kiado Zrt., 2018)
This study presents the development and validation of a new reversed-phase high-performance liquid chromatography (RP-HPLC) method for simultaneous determination of captan, folpet, and metalaxyl residues in table grape samples with ultraviolet–diode array detection (UV–DAD). Successful separation and quantitative determination of analytes was carried out on LiChrospher 60 RP-select B (250 × 4 mm, 5 μm) analytical column. Mixture of acetonitrile–0.1% formic acid in water (65:35, v/v) was used as a mobile phase, with flow rate of 1 mL/min, constant column temperature at 25 °C, and UV detection at 220 nm. The target residues were extracted with acetone by ultrasonication, followed by a cleanup using liquid–liquid extraction (LLE) and solid-phase extraction (SPE). The obtained values for multiple correlation coefficients (R2 > 0.90), relative standard deviation (RSD) of retention times, peak areas and heights (RSD ≤ 2.25%), and recoveries ranging from 90.55% to 105.40%, with RSD of 0.02% to 5.37%, revealed that the developed method has a good linearity, precision, and accuracy for all analytes. Hence, it is suitable for routine determination of investigated fungicides in table grape samples.
Keywords: RP-HPLC, UV–DAD, captan, folpet, metalaxyl, table grape